Planning for the Making of Scheduling Block Fore Peak 300 Feet Barge Using the Critical Path Method (CPM) - Rizky Hidayat (CIB Nusantara, 2025)
In the repair of a vessel, project management is essential to facilitate the distribution of tasks so that they are structured and aligned with the planned schedule. This research aims to redesign the scheduling of the fore peak block construction on a 300-feet barge, which is a critical component of the ship’s structure. The study is motivated by project delays that occurred at a shipyard in the Riau Islands, where there was a difference between the planned duration of 88 days and the actual realization of 107 days. The method used is the Critical Path Method (CPM), which can identify the critical path in the work network, calculate the earliest and latest start and finish times (ES, EF, LS, LF), and determine float values. Data processing was carried out through S-curve analysis and man-hour evaluation. The calculation results of Man-hours show 1264 JO in the planning stage and 1552 JO in the actual stage, where the increase in man-hours impacted cost escalation. Therefore, rescheduling was performed, resulting in a reduced project duration of 93 days and a decrease in the number of critical paths from 11 to 8. The implementation of CPM has proven to improve the effectiveness of project control, making it a relevant and practical method in modern ship construction project management.